Infection of wild-type Autographa californica multicapsid nucleopolyhedrovirus induces in vivo apoptosis of Spodoptera litura larvae - Zhang, Ping; Yang, Kai; Dai, Xiaojiang; Pang, Yi; Su, Deming (Journal of General Virology, 2002)
Direct evidence of in vivo apoptosis of Spodoptera litura larvae was demonstrated by haemocoel inoculation with wild-type Autographa californica multicapsid nucleopolyhedrovirus (AcMNPV) budded virus (BV). In sharp contrast to natural infection, cadavers did not melt, liquefy and melanize. Typical morphological changes of apoptosis in insect haemocytes post-infection, including blebbing of the cell surface, chromatin margination and condensation, vacuolization of the cytoplasm and formation of apoptotic bodies, were observed by light and electron microscopy. Total DNAs extracted from virus-infected haemocytes showed DNA ladders. Cleavage of chromatin DNA by endogenous endonucleases were detected in the cells of most tissues cells, including epithelial cells and fat body cells, using terminal dUTP nick end labelling assays. Virogenic stroma and viral nucleocapsids could be seen in the nuclei of a few haemocytes. Yields of BV and OV (occluded virus) produced from the infected S. litura larvae were much lower than from the infected S. exigua larvae. These data suggest that host apoptotic responses to virus infection reduce AcMNPV spread at the level of the organism and that apoptosis could be a host-range limiting factor for baculovirus infections.